Feeding Sheep Cobalt and Oregano Essential Oil Alone or in Combination on Ruminal Nutrient Digestibility, Fermentation, and Fiber Digestion Combined With Scanning Electron Microscopy - Jiao, Ting; Wu, Jianping; Casper, David P.; Davis, Delmer I.; Brown, Michael A.; Zhao, Shengguo; Liang, Jianyong; Lei, Zhaomin; Holloway, Bill (Frontiers in Veterinary Science, 2021)
The feeding of Co lactate (Co), an essential oil blend (EO; oregano), or a combination of Co and EO (EOC) may improve nutrient digestion of corn silage-based rations. In four separate studies, Co, EO, or EOC was fed at 0, 4, and 7 g/days to nine rumen fistulated rams arranged in a replicated 3 × 3 Latin square design. The fourth study evaluated the carrier at 0, 4, and 7 g/day. In each ram, fresh ensiled corn silage, leaf, and husk were placed in individual nylon bags inserted through the ruminal cannula and removed after 48 h. Rams fed increasing carrier rates demonstrated similar (P > 0.10) nutrient digestibilities and ruminal pH and volatile fatty acid concentrations. Feeding Co at 4 and 7 g/day increased (P < 0.05) digestibility of DM (59.4, 63.9, and 62.4% for 0, 4, and 7 g/day, respectively), NDF (59.4, 63.9, and 62.4%), and hemicellulose (HC; 56.2, 63.6, and 65.9%) compared with rams fed 0 g/day, while CP digestibility (46.4, 49.9, and 57.8%) was improved (P < 0.05) in rams fed 7 g/day compared with those fed 0 and 4 g/day. Rams fed 4 g/day EO digested greater (P < 0.05) HC (64.1, 71.4, and 69.1%) than rams fed 0 g/day, while rams fed 7 g/day were intermediate and similar (P > 0.10). Rams fed the EOC combination at 4 and 7 g/day demonstrated greater (P < 0.05) digestibilities of DM (57.7, 60.0, and 60.0%), NDF (21.4, 28.8, and 27.7%), and ADF (24.3, 33.3, and 34.4%) than rams fed 0 g/day. The SEM and SM techniques visually demonstrated minor evidence of husk and leaf digestibility in rams across the three experiments when fed 0 g/day of Co, EO, or EOC; rams fed 4 g/day of Co, EO, or EOC exhibited varying visual signs of leaf digestion with some palisade tissue, spongy tissue, and whole vein structure remaining, while in rams fed 7 g/day, only the vein structure remained. Results demonstrated that feeding Co, EO, or EOC at 4 or 7 g/day enhanced ruminal nutrient digestion and fermentation parameters, which was visually confirmed via SEM and SM.